Plankton Concentration Model Consistent with Natural Events and Monitoring Series of Holographic Measurements - Victor Dyomin; Daria Kurkova; Alexandra Davydova; Igor Polovtsev; Sergey Morgalev (Journal of Marine Science and Engineering)
This paper considers the features of a time series of plankton concentrations, which are further compared with such phenomena as the alteration of day and night and tidal processes. The analysis of experimental data recorded as a result of long-term monitoring measurements under field conditions showed that the diurnal variability in plankton concentrations can be described using a model harmonic function. At the same time, based on the parameters of the diurnal variability model, it is possible to build a bioindication system to detect the influence of abnormal environmental factors estimated as pollution. This study discusses the ideology of building such a system based on regular observations of the behavior of autochthonous plankton using a submersible digital holographic camera.